Successful administration of recombinant human antithrombin in a pregnant Japanese woman with hereditary antithrombin deficiency - Yuya Fujibe; Tasuku Mariya; Masahito Mizuuchi; Shinichi Ishioka; Masahiro Yoshida; Tsuyoshi Saito (Elsevier, 2019)
Objective: Hereditary antithrombin (AT) deficiency increases the risk of venous thromboembolism (VTE) in pregnant woman. We report the first case of administration of recombinant human antithrombin (rhAT) to a pregnant Japanese woman with AT deficiency. Case report: A 30-year-old woman, gravida 2 para 0, was referred to our hospital because of AT deficiency. Unfractionated heparin was administered from 13 weeks of gestation and rhAT was administered from labor onset. A cesarean section was performed and the patient and her baby were healthy, with no sequelae. Conclusion: We concluded that rhAT was effective for preventing VTE during delivery, with no potential infection risks. Keywords: Hereditary antithrombin deficiency, Pregnancy, Prophylaxis, Recombinant human antithrombin, Venous thromboembolism